Determination of chicken white and red meat mixture grinding process optimal conditions to increase meat water fixing ability - Stukalska (Ivanova), Nataliia; Sylka, Iryna (My University, 2020)
Purpose of this study is to determine regressive dependence of water fixing ability of chicken white and red meat mixture (filet + leg) upon process conditions, which may be used for verification of effect of grinding process parameters and prediction of water fixing ability increase due to certain process parameters. During research it has been used Box-Wilson method active experiment plan, which permits to save labor cost of research.
Keywords: chicken; minced meat; meat products; moisture binding; курятина; фарш; м’ясні вироби; вологозв’язуюча здатність; кафедра технології ресторанної і аюрведичної продукції